Increasing vitamin D deficiency in children from 1995 to 2011 - Seo, Ji-Hyun; Chung, Hye Jin; Kim, Hye-Jung; Yeom, Jung Sook; Park, Ji Sook; Park, Eun-Sil; Lim, Jae-Young; Park, Chan-Hoo; Woo, Hyang-Ok; Youn, Hee-Shang; Park, Jun-Je (The Turkish Journal of Pediatrics, 2016)
Serum concentrations of 25-hydroxy vitamin D 3 [25(OH)D3] and vitamin D deficiency have changed over time in Korean children. This study assessed serum 25(OH)D3 concentrations and the prevalence of vitamin D deficiency in children. Serum samples were obtained during 1995 to 2011, and 25(OH)D3 concentrations were measured by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Tests of 948 serum samples showed that median 25(OH)D 3 concentrations decreased significantly (P < 0.001), and the rates of vitamin D deficiency/insufficiency increased significantly (P < 0.001), over 15 years. Median serum 25(OH)D 3 was significantly higher in males than in females in 2005-2006 and 2010-2011 (P < 0.001), whereas the rates of vitamin D deficiency/insufficiency were higher in subjects aged 11-15 years than in the other two age groups after the year 2000. These increases over time in vitamin D deficiency/insufficiency may be due to the changing lifestyles of children. Outdoor physical activity should be strongly encouraged.